Biophysics of Water Proceedings of a working Conference held at Girton College Cambridge June 29-July 3, 1981 - Editor: Felix Franks (Chichester:John Wiley & Son Ltd, 1982)
Koleksi Referensi (Tidak Dipinjamkan)